A Comparison of Methods for the Measurement of Activated Factor VII - Kitchen, S; Malia, R G; Preston, F E (Thrombosis and Haemostasis, 1992)
A number of different methods are available for the measurement of factor VIIa. Almost all of these employ ratios of two different measurements of factor VII. In order to determine which is the most sensitive to activated factor VII we have compared currently available methods in the following groups: two patients with haemophilia A following treatment with activated recombinant factor VII (rVII a); 6 normal plasmas during cold promoted activation of factor VII; normal individuals (n = 23); and patients with unequivocal disseminated intravascular coagulation (DIC, n = 19). Factor VII was measured in an amidolytic assay (VII: Amid) and an antigen assay (VII:Ag). Clotting activity was measured using rabbit (VII:C Rab), human (VII:C Hum) and bovine (VII:C Bov) thromboplastin.Of the clotting assays the most sensitive to the presence of factor VIIa was that which utilised bovine thromboplastin. Amidolytic and immunological measurements were unaffected by the activity state of factor VII. The ratios VII:C Rab/VII: Ag and VII:C Rab/VII:Amid were insensitive to activated factor VII. The ratios most sensitive to the presence of factor VII a were VII:C Bov/VII: Amid and VII: C Bov/VII:Ag. The ratios VII:C Bov/VII:C Rab and VII:C Bov/VII:C Hum are less sensitive but have the advantage for epidemiological studies of narrower reference ranges.